The Economic Preferences of Cooperative Managers - Guillermo Alves; Pablo Blanchard; Gabriel Burdín; Mariana Chávez; Andres Dean (Institute of Labor Economics (IZA), 2019)
A growing body of research has been investigating the role of management practices and managerial behaviour in conventional private firms and public sector organizations. However, little is known about managers' behavioural profile in noninvestor-owned firms. This paper aims to fill this gap by providing a comprehensive behavioural characterization of managers employed in cooperatives.We gathered incentive-compatible measures of risk preferences, time preferences, reciprocity, altruism, and trust from 196 Uruguayan managers (half of them employed in worker cooperatives) and 92 first-year undergraduate students. To do this, we conducted a high-stakes lab-in-the-field experiment in which participants played a series of online experimental games and made incentivised decisions. The average payoff in the experiment was approximately 2.5 times higher than the average local managerial wage in the private sector. Our key findings are that (1) the fraction of risk loving subjects is lower among co-op managers compared to conventional managers, and (2) co-op managers appear to be more altruistic than their conventional counterparts. Interestingly, we do not observe significant differences between the two groups across other preference domains, such as impatience, trust, and reciprocity.
Keywords: C90; D81; J54; 330; risk-aversion; time preferences; altruism; reciprocity; trust; lab-in-the-field experiment; managers; cooperatives